Passive control applied to structural optimization and dynamic analysis of a space truss considering uncertainties - Pires, F. A. [UNESP]; Goncalves, P. J. P. [UNESP]; Sas, P.; Moens, D.; VanDeWalle, A. (Katholieke Univ Leuven, Dept Werktuigkunde, 2016)
Due to the need for monitoring Earth's natural systems, fleets of satellites will be launched in the next few years. In order to minimize shuttle launch costs, space structures should have the shape of trusses because of the significant weight reduction by being assembled with elements made of light materials (e.g. aluminum). For this reason, a control method must be applied to maintain the requirements of vibration levels in these types of structures. This work applies a passive vibration control to a space lattice structure utilizing the Finite Element Method (FEM) in order to predict and compare the system's frequency response functions (FRFs). The optimization technique simulated annealing (SA) is also applied to the structure to find the coordinates of each node of the space truss that minimize the value of norm H-2 for each mode of vibration. The Monte Carlo technique is also applied so it is possible to come up with an envelope function to show whether or not the FRFs are inside it.